BIOMASS PRODUCTION, GROWTH RATE, AND CARRAGEENAN CONTENT OF Kappaphycus alvarezii PERFORMED BY VERTICULTURE METHOD WITH DIFFERENT INITIAL WEIGHT - Agus Kurniawan B; Asriani Asriani; Muhammad Subhan Hamka (AQUASAINS, 2023)
Kappaphycus alvarezii seaweed is important for the processing industry because it contains carrageenan used as a stabilizer, thickener, material forming an emulsifier. This study aimed to find the best and optimal initial seed weight treatment for maximum biomass production, growth rate, and carrageenan content. The research location was in the waters of Aeng Batu-Batu Village, Takalar Regency, South Sulawesi in August-September 2022. The randomized block design method (RAK) consisted of 4 treatments each with 4 repetitions. Seaweed seedlings from spores were weight of 20 g, 40 g, 60 g, and 80 g planted at 60 cm depth respectively and maintained for 45 days. Data analysis used (ANOVA) and W-Tuckey to determine the differences between treatments. The result of the analysis of variences showed that the weight of 40 g, 60 g, and 80 g had an effect on the biomass production, growth rate, and K. alvarezii carrageenan content. However, the highest yield was obtained at a weight of 20 g which had a very significant effect (p<0.01).